Pharmacokinetics of Ursodeoxycholic Acid in Elderly Volunteers Compared With Younger Adults in a Korean Population. (18th March 2019) - Lee, Soyoung; Yoon, Seonghae; Chung, Hyewon; Ji, Sang Chun; Yoon, Seo Hyun; Yu, Kyung‐Sang; Cho, Joo‐Youn; Chung, Jae‐Yong
Abstract: Ursodeoxycholic acid (UDCA) is a secondary bile acid component used for treating primary biliary cirrhosis. This study evaluated and compared the pharmacokinetic (PK) profiles of UDCA and its conjugates glyco‐UDCA (G‐UDCA) and tauro‐UDCA (T‐UDCA) in healthy elderly subjects and younger adults. In this randomized, open‐label, 2‐treatment, 1‐sequence, and parallel study, subjects received 400 or 800 mg UDCA on day 1, followed by 200 mg UDCA twice daily for 2 weeks. Blood samples were obtained up to 24 hours after the first UDCA dose. Changes in miRNA‐122, γ‐glutamyl transferase, aspartate aminotransferase, and alanine aminotransferase levels from baseline were assessed to determine the safety and pharmacological effects of UDCA. This study examined the outcomes of 16 elderly subjects and 16 younger adults. Dose‐normalized peak concentration of and systemic exposure to UDCA were 2 to 4 times higher, and the corresponding values of G‐UDCA and T‐UDCA were 1.7 times higher in the elderly subjects than in the younger adults. The subjects in both groups showed multiple peak profiles of UDCA and its conjugates. The miRNA‐122 levels and hepatic enzyme test results were within the normal range in the elderly subjects after multiple administration of UDCA. This study is the first to confirm that the PK measurements of UDCA were higher in elderly subjects than in younger adults, which may improve the clinical outcomes of elderly subjects.